The running and technical performance of U13 to U18 elite japanese soccer players during match play - Goto, H.; Saward, C. (The Journal of Strength and Conditioning Research, 2020)
The aims of the current study were (a) to examine age-related differences in match running performance with 2 different approaches (speed vs. metabolic power) in U13-U18 Japanese elite soccer players and (b) to examine age-related differences in technical match performance in U13-U18 Japanese elite soccer players. Participants were 110 outfield players from academies of 2 professional soccer clubs in Japan. Forty-eight 11-a-side official league matches (13, 6, 9, 7, 6, and 7 matches for U13, U14, U15, U16, U17, and U18 age-groups, respectively) were analyzed (152 complete match files). Global positioning system (15 Hz) and video analysis were used to analyze running and technical performance during matches, respectively. Total distance covered in absolute terms (U13 < [U14 and U15] < [U16-U18]; p < 0.05 for all), high-intensity running distance ([U13-U15] < [U16-U18]; p < 0.05 for all), and distance covered during the metabolic power zone of =35 W/kg relative to match playing time ([U13 < U16], [U13-U15] < [U17 and U18]; p < 0.05 for all) increased with age. The speed zone based approach (high-intensity running distance, =4.0 m/s) underestimated high-intensity demands compared with the metabolic power zone based approach (=20 W/kg) by ~33 to ~57% (p < 0.01 for all), with the underestimation declining with age (p < 0.001). Pass accuracy improved with age from 73% at U13 to 85% at U18 (p < 0.001). Therefore, distance covered at high speeds and at high metabolic powers, and pass accuracy increase with age. Moreover, the speed zone based approach underestimates the demands of match play in Japanese elite youth soccer players. The current results could support coaches to develop players, identify talent, and produce age-specific training programs.